DISTRIBUTION ANALYSIS OF SPECIES BELONGING TO THE INULA L. GROUP DISTRIBUTED IN CENTRAL ASIA IN ECOLOGICAL REGIONS (Scientific journal of the Fergana State University, 2024)
This article presents analyzes of the results of studies on the distribution of Inula glauca C.Winkl., Inula grandis Schrenk ex Fisch. & C.A.Mey., Inula helenium L, Inula macrolepis Bunge, Inula rhizocephala Schrenk ex Fisch. & C.A.Mey., Inula rhizocephala Schrenk ex Fisch. & C.A.Mey., which are representatives of the Inula L. genus distributed in Central Asia, by ecoregions.